Prevalence of functional somatic syndromes and bodily distress syndrome in the Danish population: the DanFunD study. Issue 5 (July 2020) - Petersen, Marie Weinreich; Schröder, Andreas; Jørgensen, Torben; Ørnbøl, Eva; Dantoft, Thomas Meinertz; Eliasen, Marie; Carstensen, Tina Wisbech; Falgaard Eplov, Lene; Fink, Per
Aims: Little is known about the prevalence and characteristics of functional somatic syndromes (FSS) such as irritable bowel syndrome (IBS), fibromyalgia (FM), chronic fatigue syndrome (CFS), whiplash associated disorders (WAD), multiple chemical sensitivity (MCS), and bodily distress syndrome (BDS) in the general population when they are investigated simultaneously. Method : This cross-sectional study is based on the Danish Study of Functional Disorders (DanFunD) cohort consisting of 9656 adults from the general population. FSS and BDS were identified by questionnaires and characterized by age, sex, vocational training, physical health and comorbidity with physical and psychiatric disease. Results : In total, 16.3% (95% CI: 15.6–17.1) of the participants fulfilled the criteria for at least one FSS, ranging from 1.7% for WAD to 8.6% for CFS, and 16.1% (95% CI: 15.4–16.9) fulfilled the criteria for BDS. Cases had a high risk of poor self-perceived health, limitations in daily activities, and a high psychiatric comorbidity, all increasing with the number of syndromes in each individual. However, the associations differed across the various FSS. Mutual overlaps of IBS, FM and CFS were greater than could be expected by chance. Conclusions : FSS and BDS are prevalent in the adult Danish population, and cases have high risk of poor self-perceived health, limitation in daily activities, and psychiatric comorbidity. These associations were particularly strong for cases with multiple FSS and multi-organ BDS.